Islam Nusantara in the Traces of Kelopo Telu: Memories of the Kapu Merakurak Civilization - Nurul Hakim; Fitri Minhatus Saniyah; Wahyu Isnatur Rohmah; Siti Suhailah (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aims to examine the traces of Nusantara Islam in the history of Kelopo Telu in Kapu Village, Merakurak District, Tuban Regency, and to observe how the memory of this civilization remains alive in the community's traditions to this day. Kelopo Telu is closely linked to Kiai Sholeh, a cleric who played a significant role in the spread of Islam in the region. This study uses a qualitative approach with historical and descriptive study methods through an analysis of local traditions, historical sites, and religious practices that developed in the community. The results show that the existence of Kelopo Telu not only has historical significance as a symbol of Islamic preaching, but also forms part of the religious identity of the Kapu community. This spiritual heritage is still preserved through the traditions of pilgrimages, commemorations of the haul (haul), earth almsgiving, and the existence of educational institutions that carry on Kiai Sholeh's preaching spirit. Thus, Kelopo Telu represents the acculturation process between Islamic values and local culture, reflecting the moderate, contextual, and traditional character of Nusantara Islam.